2009
DOI: 10.1016/j.sbi.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides in cell recognition and membrane protein regulation

Abstract: Summary Gangliosides, sialic acid-bearing glycosphingolipids, are expressed on all vertebrate cells, and are the major glycans on nerve cells. They are anchored to the plasma membrane through their ceramide lipids with their varied glycans extending into the extracellular space. Through sugar-specific interactions with glycan binding proteins on apposing cells, gangliosides function as receptors in cell-cell recognition, regulating natural killer cell cytotoxicity via Siglec-7 binding, myelin-axon interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
202
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(206 citation statements)
references
References 57 publications
(47 reference statements)
0
202
0
4
Order By: Relevance
“…It is commonly known that gangliosides are associated or complexed with signal transducers such as small G-proteins, Src family kinases, tetraspanins, and integrins (28). The modulation of ganglioside expression can therefore have deep effects on receptormediated signaling, notably RTKs, and regulate cell growth through inhibition/activation of signal transduction pathways (15)(16)(17). For example, tyrosine kinase activity of EGFR is inhibited by the monosialoganglioside G M3 through carbohydrate-carbohydrate interactions of G M3 with GlcNAc terminated N-glycan on EGFR, without interfering with EGF binding (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly known that gangliosides are associated or complexed with signal transducers such as small G-proteins, Src family kinases, tetraspanins, and integrins (28). The modulation of ganglioside expression can therefore have deep effects on receptormediated signaling, notably RTKs, and regulate cell growth through inhibition/activation of signal transduction pathways (15)(16)(17). For example, tyrosine kinase activity of EGFR is inhibited by the monosialoganglioside G M3 through carbohydrate-carbohydrate interactions of G M3 with GlcNAc terminated N-glycan on EGFR, without interfering with EGF binding (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cellular ganglioside composition can modulate the activity of growth factor receptors, and consequently induce the activation of intracellular molecular pathways (15)(16)(17). In this context, the phosphorylation status of 42 RTKs was simultaneously examined using a phospho-RTK array in MDA-MB-231 cells.…”
Section: C-met Receptor Is Constitutively Activated In G D3 Synthase-mentioning
confidence: 99%
“…Хоча у більшості клітин основу глікокаліксу формують глікопротеїни та протеоглікани, а гліколіпіди переважають лише у плазмалемі клітин нервової тканини, проте вони завжди присутні й у інших тканинах і є молекулами посередниками міжклітинних взаємодій у різних тканинах [1]. Одними із ключових сполук у мережі міжклітинних взаємодій є глікосфінголіпіди, серед яких вирізняється клас сіалованих гліколіпі дів -гангліозиди.…”
Section: вступunclassified
“…сіалозв'язуючий лектин І типу сіглек 7 [2], беруть участь у регенерації мієлінового шару, взаємодіючи через мієлін асоційований глікопротеїн [1,3], можуть регулюва-ти активність рецепторів інсуліну та ЕФР, взаємодіючи із тирозинкіназними доме-нами [3,4], є лігандами, що розпізнаються різними токсинами прокаріот, а також можуть брати участь у розпізнаванні клітин макрофагами. Біосинтез гангліозидів [5], який у спрощеному вигляді представлено на рис.1, сприяє різноманітності мож-ливих гліканових ланцюгів цих молекул.…”
unclassified
“…Sialylated lipooligosaccharide (LOS) is widely present in bacteria, including Neisseria gonorrhoeae, Campylobacter, Pasteurella and Luminescent Bacteria [912]. Sialylation is not only involved in the stability of protein structure, but also in extension of the half-life of glycoproteins; moreover, it is an important component in many biological processes, such as cell recognition [13], leukocyte homing [14], cell adhesion and invasion [15] and cell signaling [16]. The genes involved in sialic acid metabolism have been investigated in 21  H. parasuis strains from different clinical origins (including nasal and systemic isolates).…”
Section: Introductionmentioning
confidence: 99%